Differential sclerostin and parathyroid hormone response to exercise in boys and men. Issue 3 (March 2016) - Falk, B.; Haddad, F.; Klentrou, P.; Ward, W.; Kish, K.; Mezil, Y.; Radom-Aizik, S.
Abstract Summary Physical exercise benefits bone structure and mineralization, especially in children. Immediately following high-impact exercise, PTH increased and returned to resting values within 24 h in both groups, while sclerostin increased in men but not in boys. The underlying mechanisms and implication of this age-related differential response are unclear. Introduction Circulating sclerostin, a negative regulator of bone, decreases during puberty and increases in adulthood. Parathyroid hormone (PTH) is inversely related to sclerostin. In mice, sclerostin decreases following 24 h of mechanical stimulation. Its response to exercise in humans and, especially in children, in whom high-impact physical exercise benefits bone structure and mineralization is unclear. The aim of this study was to investigate the acute response of sclerostin to a single exercise session of high mechanical loading and the corresponding changes in PTH in boys and men. Methods Twelve boys (10.2 ± 0.4 years old) and 17 young men (22.7 ± 0.8 years old) underwent a protocol of plyometric exercises (total 144 jumps). Blood samples were collected pre-, 5 min, 1 h, and 24 h post-exercise. Results Boys had significantly higher resting values of sclerostin compared with men (150 ± 37 vs. 111 ± 34 pg/ml, respectively, p  = 0.006). Following exercise, sclerostin markedly increased in men but this response was attenuated in boys (at 5 min: 51 ± 38 vs. 14 ± 21 %, respectively, p  = 0.005). PTH levels were similar in boys and men at rest and throughout the 24-h study period, increasing significantly (p  < 0.001) 5 min after exercise, decreasing after 60 min post-exercise and returning to resting values within 24 h. Conclusion Although the PTH response was similar in boys and men, the sclerostin response was greater in men. The combined increases in PTH and sclerostin immediately post-exercise appear contrary to the accepted osteogenic effect of exercise. The underlying mechanisms and full implication of the differential response between children and adults need to be further examined.